تقييم مستوى اللياقة البدنية لدى طلبة سنة ثالثة اختصاص كرة القدم في معهد علوم وتقنيات النشاطات البدنية والرياضية لجامعة باتنة -02- - شريط, حسام الدين; قادري, عبد الحفيظ; محمدي, مهدي (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة إلى التعرف على مستوى اللياقة البدنية لدى الطلبة ووضع درجات ومستويات معيارية للياقة البدنية للطلبة، وقد استخدمنا المنهج الوصفي التحليلي باختيار عينة الدراسة من الفئة المستهدفة بالطريقة القصدية، وقد بلغ حجم عينة الدراسة 41 طالب من فئة الراشدين، اختصاص كرة القدم من معهد علوم وتقنيات النشاطات البدنية للموسم الجامعي 2018/2019 بجامعة باتنة 2، وبعد تطبيق الاختبارات البدنية، عولجت البيانات إحصائيا باستخدام البرنامج الإحصائي. وبينت النتائج الى تحقيق العينة في اختبار التحمل والرشاقة المستوى الجيد، كما حققت العينة في اختبار المرونة المستوى المتوسط، بينما حققت العينة في اختبار السرعة والقوة المستوى الضعيف.: The study aimed at identifying the students ’physical fitness level and setting grades and standard levels of physical fitness for students. We used the descriptive analytical approach by selecting the study sample from the target group in the intentional way. The study sample size reached 41 students from the adult category, specializing in football from the Institute of Science and Technology Physical activities for the sports season 2018/2019 at the University of Batna 2, and after applying the physical tests, the data were statistically treated using the statistical program. The results showed that the sample in the endurance and agility test achieved a good level, and the sample in the flexibility test achieved the medium level, while the sample in the speed and strength test achieved the weak level.
Assessment of the level of physical fitness of third year students football specialty at the Institute of Science and Techniques of Physical and Sports Activities of the University of Batna -2
مقال
Keywords: اللياقة البدنية، كرة القدم; Physical fitness, football.